2019
DOI: 10.1016/j.stem.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Bone Marrow Hematopoietic Stem Cell Niches Promotes Myeloid Cell Expansion during Premature or Physiological Aging

Abstract: SummaryHematopoietic stem cells (HSCs) residing in the bone marrow (BM) accumulate during aging but are functionally impaired. However, the role of HSC-intrinsic and -extrinsic aging mechanisms remains debated. Megakaryocytes promote quiescence of neighboring HSCs. Nonetheless, whether megakaryocyte-HSC interactions change during pathological/natural aging is unclear. Premature aging in Hutchinson-Gilford progeria syndrome recapitulates physiological aging features, but whether these arise from altered stem or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
274
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(306 citation statements)
references
References 63 publications
15
274
2
1
Order By: Relevance
“…Furthermore, the distance between HSCs and megakaryocytes regulates HSC proliferation and increases in β3adrenergic receptor (AR) mice and in natural aging. In 2019, Ho et al also identified disrupted β-adrenergic nerve signaling (increased β2-AR-interleukin (IL)-6 levels and decreased β3-AR-Nos1 activity) as an important determinant of niche alterations during aging, resulting in impaired lymphoid differentiation and myeloid expansion [113]. In addition, Frisch et al showed that dysfunction of aged marrow macrophages directed HSC platelet bias and that aged mice exhibited markedly more senescent neutrophils than young mice [11].…”
Section: Changes In the Extrinsic Hsc Niche During Agingmentioning
confidence: 99%
“…Furthermore, the distance between HSCs and megakaryocytes regulates HSC proliferation and increases in β3adrenergic receptor (AR) mice and in natural aging. In 2019, Ho et al also identified disrupted β-adrenergic nerve signaling (increased β2-AR-interleukin (IL)-6 levels and decreased β3-AR-Nos1 activity) as an important determinant of niche alterations during aging, resulting in impaired lymphoid differentiation and myeloid expansion [113]. In addition, Frisch et al showed that dysfunction of aged marrow macrophages directed HSC platelet bias and that aged mice exhibited markedly more senescent neutrophils than young mice [11].…”
Section: Changes In the Extrinsic Hsc Niche During Agingmentioning
confidence: 99%
“…Importantly, this age-related expansion of lymphocytes in the prostate happens in contrast to the agerelated myeloid bias of hematopoiesis (Mann et al, 2018). As mice age, different processes including bone marrow stem cell niche remodeling, inflammatory cytokines, and telomere dysfunction skew hematopoiesis towards myeloid lineages (Ergen et al, 2012;Ho et al, 2019;Ju et al, 2007). Aging is also associated with involution of the thymus, resulting in reduced production of naïve T cells (Palmer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related biased denervation and BM-niche remodeling lead to premature aging-like changes in murine HSCs [115]. The aging BM harbors not only reduced b3-AR signaling, but importantly also contains reduced endosteal HSC niches, which all lead to the aging-typical biased myelopoiesis [116]. Aging is also associated with a sharp decline in sex hormones and melatonin synthesis, accompanied by osteoporosis, anemia, and a major reduction in host immunity [37,117].…”
Section: Clinical Aspects Related To Disturbed Light and Darkness Cyclesmentioning
confidence: 99%